Castleman disease variant of POEMS syndrome without M protein: a case report - Ji, Min; Jin, Shumin; Zang, Shaolei; Li, Peng; Lu, Fei; Zhao, Chuanli; Zhang, Chunqing; Ji, Chunyan; Ye, Jingjing (Frontiers in Oncology, 2024)
POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, skin changes) syndrome is a paraneoplastic syndrome associated with an underlying plasma cell neoplasm. According to the current diagnostic criteria for POEMS syndrome, the presence of characteristic polyneuropathy and clonal plasma cell disorder are required for diagnosis. We report a case of a Castleman disease variant of POEMS syndrome without monoclonal protein (M protein) expression, which presented with polyneuropathy, organomegaly, endocrinopathy, skin lesions, and sclerotic bone lesions. The patient was treated with lenalidomide and dexamethasone (RD), after which her symptoms improved. The findings in this case suggest that the diagnostic criteria for POEMS syndrome might require reconsideration.